The Role of NLRP3 Inflammasome in Lupus Nephritis - Camila Barbosa Oliveira (MDPI AG, 2021)
Lupus nephritis (LN) is the most frequent and severe of systemic lupus erythematosus (SLE) clinical manifestations and contributes to the increase of morbidity and mortality of patients due to chronic kidney disease. The NLRP3 (NLR pyrin domain containing 3) is a member of the NLR (NOD-like receptors), and its activation results in the production of pro-inflammatory cytokines, which can contribute to the pathogenesis of LN. In this review manuscript, we approach the relation between the NLRP3 inflammasome, SLE, and LN, highlighting the influence of genetic susceptibility of NLRP3 polymorphisms in the disease; the main functional studies using cellular and animal models of NLRP3 activation; and finally, some mechanisms of NLRP3 inhibition for the development of possible therapeutic drugs for LN.